2020
DOI: 10.1016/j.jhep.2019.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in patients with decompensated alcohol-related liver disease, steatohepatitis and Maddrey's discriminant function <32

Abstract: We studied long-term outcome of 121 patients with acutely decompensated alcohol-related liver disease with histological steatohepatitis and Maddrey discriminant function <32. The 1 and 5-year mortality were about 20% and 50% respectively. Encephalopathy at baseline and alcohol abstinence during the follow-up were predictive factors of mortality Histological steatohepatitis 0.0 Highlights Patients with non-severe alcoholic hepatitis have a low risk of short-term mortality. The 5-year mortality of decompensated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 27 publications
6
39
0
2
Order By: Relevance
“…However, we found no statistically significant difference in 28-day mortality between patients with and without HE (p=0.071). In 90-day and 180-day mortality, it has good prognostic value (p<0.001,p=0.001) and is considered an independent risk factor (HR: 1.416, 95% CI: 1.102,1.818, p=0.007; HR: 1.328, 95% CI: 1.046,1.686, p=0.020), consistent with previous studies [ 21 , 22 ]. Monitoring of lactate levels is important in ICU patients with sepsis [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, we found no statistically significant difference in 28-day mortality between patients with and without HE (p=0.071). In 90-day and 180-day mortality, it has good prognostic value (p<0.001,p=0.001) and is considered an independent risk factor (HR: 1.416, 95% CI: 1.102,1.818, p=0.007; HR: 1.328, 95% CI: 1.046,1.686, p=0.020), consistent with previous studies [ 21 , 22 ]. Monitoring of lactate levels is important in ICU patients with sepsis [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…Since the 1960s it has been observed that abstinence from alcohol is also key for preventing death in patients with decompensated ALD [31]. This is supported by recent prospective [32] and retrospective cohort studies [33].…”
Section: Treatmentmentioning
confidence: 85%
“…Studies have shown that patients with DF ≥ 32 and no treatment have a mortality rate of 20-50% over 30 days; depending on practices of supportive care [18,19]. Current American College of Gastroenterology guidelines recommend treating AH patients with corticosteroids who have DF ≥ 32 [16,20]. Limitation of this score includes non-standardization of the PT values, and different upper value of the normal range as a laboratory variation depending on the type of thromboplastin used.…”
Section: Discriminant Function (Df)mentioning
confidence: 99%